Optimization and fault diagnosis of 132 kV substation low-voltage system using electrical transient analyzer program - Mohammed Kareem Mohammed; Mohammed Qasim Taha; Firas Fadhil Salih; Falah Noori Saeed (Institute of Advanced Engineering and Science, 2023)
In this paper, a simulation and analysis of 132 kV Substation in feeds western Iraq have been presented including a short circuit (S.C) analysis. This work helps to properly control and coordinate the protection equipment used in this grid interconnection spot. This work includes power flow analysis carried out using electrical transient analyzer program (ETAP) simulator. Also, the most common types of faults are investigated for the substation buses using International Electrotechnical Commission (IEC) and the American National Standards Institute (ANSI) standards to discover the behavioral characteristics under different scenarios for the substation transformers connection to assess the range of S.C current this substitution can ride through. Finally, the results of ANSI and IEC are theoretically investigated for validity to ensure reliability and quality assurance in the case study substation.